Surface Plasmon Resonance Based Fiber Optic Sensor: Theoretical Simulation and Experimental Realization - Sultan, Murtadha Faaiz; Al-Zuky, Ali A; Kadhim, Shehab A (Al-Nahrain Journal of Science, 2018)
Surface plasmon resonance (SPR) based fiber optic sensor with two types of plasmonic metals (gold and silver) are theoretically studied and implemented experimentally. Performance characteristics like sensitivity, signal to noise ratio, the figure of merit, and resolution are evaluated for both simulated and fabricated sensor. The results of theoretical and experimental studies and also between the sensor with the gold layer and that with silver have been compared. Sensitivity is larger for the sensor with the gold layer while the signal to noise ratio and figure of merit are larger for the sensor with the silver layer for both the experimental and theoretical studies. The resolution is slightly larger for the sensor with the gold layer and there is some difference between the resolution of the simulated and that of the fabricated sensor.